Nomi propri di persona e attitudine linguistica. Ricostruzione dell’attitudine linguistica delle persone di nome longobardo nell’Italia longobarda - Vig, István (Italogramma, 2020)
<span dir="ltr" style="left: calc(var(–scale-factor)*70.82px); top: calc(var(–scale-factor)*234.88px); font-size: calc(var(–scale-factor)*11.04px); font-family: sans-serif; transform: scaleX(0.986261);" role="presentation">Longobard personal names and language attitudes. Reconstruction of the language attitude of <span dir="ltr" style="left: calc(var(–scale-factor)*70.82px); top: calc(var(–scale-factor)*247.27px); font-size: calc(var(–scale-factor)*11.04px); font-family: sans-serif; transform: scaleX(1.02343);" role="presentation">persons with Longobard names in Longobard Italy. <span dir="ltr" style="left: calc(var(–scale-factor)*328.27px); top: calc(var(–scale-factor)*247.27px); font-size: calc(var(–scale-factor)*11.04px); font-family: sans-serif; transform: scaleX(0.938162);" role="presentation">The personal names analysed in this study <span dir="ltr" style="left: calc(var(–scale-factor)*70.82px); top: calc(var(–scale-factor)*259.87px); font-size: calc(var(–scale-factor)*11.04px); font-family: sans-serif; transform: scaleX(0.916899);" role="presentation">(with the exception of two of them) come from Latin documents (wills, sale contracts, gift agreements, <span dir="ltr" style="left: calc(var(–scale-factor)*70.82px); top: calc(var(–scale-factor)*272.59px); font-size: calc(var(–scale-factor)*11.04px); font-family: sans-serif; transform: scaleX(0.90764);" role="presentation">court judgements) written in the 8th century AD. Only the names of those persons were included in the <span dir="ltr" style="left: calc(var(–scale-factor)*70.82px); top: calc(var(–scale-factor)*285.19px); font-size: calc(var(–scale-factor)*11.04px); font-family: sans-serif; transform: scaleX(0.924038);" role="presentation">study who personally signed the document, with the exception of the name of <span dir="ltr" style="left: calc(var(–scale-factor)*422.35px); top: calc(var(–scale-factor)*285.19px); font-size: calc(var(–scale-factor)*11.04px); font-family: sans-serif; transform: scaleX(0.91049);" role="presentation">the document’s <span dir="ltr" style="left: calc(var(–scale-factor)*493.66px); top: calc(var(–scale-factor)*285.19px); font-size: calc(var(–scale-factor)*11.04px); font-family: sans-serif; transform: scaleX(0.91679);" role="presentation">author, <span dir="ltr" style="left: calc(var(–scale-factor)*70.82px); top: calc(var(–scale-factor)*297.91px); font-size: calc(var(–scale-factor)*11.04px); font-family: sans-serif; transform: scaleX(0.918345);" role="presentation">which was included also in case he was illiterate. The Longobard names were used in the documents <span dir="ltr" style="left: calc(var(–scale-factor)*70.82px); top: calc(var(–scale-factor)*310.51px); font-size: calc(var(–scale-factor)*11.04px); font-family: sans-serif; transform: scaleX(0.927464);" role="presentation">in their original Longobard form or in a Latinised one. <span dir="ltr" style="left: calc(var(–scale-factor)*70.82px); top: calc(var(–scale-factor)*323.11px); font-size: calc(var(–scale-factor)*11.04px); font-family: sans-serif; transform: scaleX(0.92067);" role="presentation">The Longobard names are used in their original form by both secular and clerical bearers. The use of <span dir="ltr" style="left: calc(var(–scale-factor)*70.82px); top: calc(var(–scale-factor)*335.83px); font-size: calc(var(–scale-factor)*11.04px); font-family: sans-serif; transform: scaleX(0.954964);" role="presentation">the original Longobard names or of their Latinised forms wa<span dir="ltr" style="left: calc(var(–scale-factor)*348.67px); top: calc(var(–scale-factor)*335.83px); font-size: calc(var(–scale-factor)*11.04px); font-family: sans-serif; transform: scaleX(0.941941);" role="presentation">s conditioned by their bearers’ attitude <span dir="ltr" style="left: calc(var(–scale-factor)*70.82px); top: calc(var(–scale-factor)*348.43px); font-size: calc(var(–scale-factor)*11.04px); font-family: sans-serif; transform: scaleX(0.902417);" role="presentation">towards the Longobard language and spoken Late Latin, respectively.